EFFECT OF KIWIFRUIT ON METABOLIC HEALTH - Poolsup, Nalinee; Suksomboon, Naeti; Lin, Wei (Interprofessional Journal of Health Sciences, 2023)
Kiwifruit is known as “Actinidia” containing antioxidants, fiber, vitamins that seems beneficial for metabolic health. The purpose of this study was to systematically evaluate the effect of kiwifruit on metabolic health. Literature search was conducted on PubMed, Web of Science, Cochrane Central Register of Controlled Trials (CENTRAL), Scopus, ScienceDirect, Cumulative Index to Nursing and Allied Health Literature (CINAHL), Proquest, Latin American and Caribbean Health Sciences Literature (LILACS), International Clinical Trials Registry Platform (ICTRP), Australia New Zealand Clinical Trials Registry (ANZCTR), ClinicalTrials.gov, Clinical Trial Results, China National Knowledge Infrastructure (CNKI) and Wanfang Standards Database (WFSD) up to November 2017 without language restriction. European Association for the Study of Diabetes (EASD) and American Diabetes Association (ADA) conferences were also searched. Randomized controlled trials (RCTs) which compared kiwifruit with placebo or no pharmacotherapy were included. The outcomes were fasting plasma glucose (FPG), glycosylated hemoglobin (A1C), 2-hour postprandial glucose (2h-PG), body weight (BW), homeostasis model assessment of insulin resistance (HOMA-IR), blood pressure (BP), total cholesterol (TC), triglyceride (TG), high-density lipid (HDL), and low-density lipid (LDL). Quality of studies was assessed by Cochrane risk of bias tool. Among 639 studies identified, 4 RCTs were included in this systematic review involving 85 hypercholesterolaemic men patients, 178 hypertensives and 122 diabetes patients. Three studies were in English language and one study was in Chinese language which was translated into English. Based on those evidences, kiwifruit seems to have positive effects on metabolic health with improvement of HDL.